2021
DOI: 10.1007/s00405-021-06956-6
|View full text |Cite
|
Sign up to set email alerts
|

Hearing recovery after surgical resection of non-vestibular schwannoma cerebellopontine angle tumors

Abstract: Purpose: Post-operative outcomes for hearing after resection surgery to remove cerebellopontine angle (CPA) tumors other than vestibular schwannomas (VS) are not well understood. This study presents a series of patients with significant postoperative hearing recovery, trying to define the incidence among all patients operated on for removal of non-VS CPA tumors. Methods: This is a retrospective observational case series of 8 patients among 69 operated on for removal of non-VS CPA tumors between 2012 and 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Whether the canal is involved is signi cant because removal of tumors involving the IAC potentially exposes the facial nerve and cochlear nerve to increased risk of injury during surgical tumor removal. In terms of preservation of hearing function in CPA meningioma, previous studies have suggested that surgery should always be considered regardless of pre-operative hearing status [2].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the canal is involved is signi cant because removal of tumors involving the IAC potentially exposes the facial nerve and cochlear nerve to increased risk of injury during surgical tumor removal. In terms of preservation of hearing function in CPA meningioma, previous studies have suggested that surgery should always be considered regardless of pre-operative hearing status [2].…”
Section: Introductionmentioning
confidence: 99%